The African Union-China strategic partnership : prospects and challenges of aligning Africa's agenda 2063 and China's vision 2049 - Nshimbi, Christopher Changwe (University of Pretoria, 2023)
Thesis (PhD (International Relations))--University of Pretoria, 2023.